2022
DOI: 10.1002/admt.202101358
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development and Applications of Advanced Materials via Direct Ink Writing

Abstract: the hydrogel. Although extensive efforts have been devoted to this endeavor, most studies are still in the fundamental laboratory scale. Only a few real applications in the areas of energy storage (lithium ion batteries [LIBs], supercapacitor) and energy conversion (fuel cell) have been reported. [6][7][8] As a result, the development of new technology to fabricate advanced materials may provide a breakthrough in the limitations of traditional fabrication techniques for nanomaterial-based device preparation.Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 157 publications
0
12
0
Order By: Relevance
“…The open porosity ( P , %) and bulk density (ρ, g cm −3 ) of composite ceramic were measured by Archimedes drainage method [ 23 ] P=M3M1M3M2×100%ρ=M1×DnormalLM3M2where D L (g cm −3 ) is the density of the water in the test process, M 1 (g) and M 2 (g) are the weight of composite ceramic before and after in water, respectively. M 3 is the weight of the composite ceramic filled with water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The open porosity ( P , %) and bulk density (ρ, g cm −3 ) of composite ceramic were measured by Archimedes drainage method [ 23 ] P=M3M1M3M2×100%ρ=M1×DnormalLM3M2where D L (g cm −3 ) is the density of the water in the test process, M 1 (g) and M 2 (g) are the weight of composite ceramic before and after in water, respectively. M 3 is the weight of the composite ceramic filled with water.…”
Section: Methodsmentioning
confidence: 99%
“…The open porosity (P, %) and bulk density (ρ, g cm À3 ) of composite ceramic were measured by Archimedes drainage method [23]…”
Section: Micro-structural Characterizationmentioning
confidence: 99%
“…Studies have demonstrated that when Oh is between 0.1 and 1, smooth DIW processes can be achieved. [131,135] When Oh exceeds 1, the printing process may be affected by excessive viscous resistance, resulting in the blockage of extrusion nozzles. When Oh is less than 0.1, the inks cannot sustain sufficient viscoelasticity to form filaments, and they break apart upon contact with the substrate, forming satellite droplets.…”
Section: Printabilitymentioning
confidence: 99%
“…On the other hand, the three-dimensional (3D) direct printing technique has recently been developed for fabricating various kinds of microdevices, which provides the comprehensive advances of direct pattern writing, fast device prototyping, and a simplified fabrication process. By taking advantage of both the digital programming and automated manufacturing, the 3D direct printing technique is capable of obtaining rationally designed device structures with accurately controlled spatial geometries from the microscale even down to the nanoscale. However, up to now little work has been done to fabricate the zinc-air microbatteries by using the 3D direct printing technique, which is mainly ascribed to the challenges in both the preparation of the active electrode inks with complicated composition of the nano/micromaterial catalysts and conducting/binding agents in solvent and the formation of the solid electrode/liquid electrolyte/gas air three-phase interfacing structure in the porous air electrode. Zhang et al successfully fabricated the air and zinc electrode sheets by using the 3D direct printing technique and assembled the solid-state zinc-air battery by sandwiching a poly­(vinyl alcohol) (PVA)-based gel electrolyte in middle . In the work, the conventional sandwich-type device configuration was adopted, which cannot be used for making microenergy devices.…”
Section: Introductionmentioning
confidence: 99%